Efficacy of Seed Priming through Plant Hormones on the Germination of Bitter Melon (Momordica charantia L.): Hormonal seed priming effects on germination - Abdulhamza Muttaleb, Qusay; Shahmukh, Ahmed Fali; Mohsen, Dunia Mohi (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Bitter melon (Momordica charantia L.) is a fast-growing vine and seeds germinated quickly in warm soil even if covered with shaded by crops. Due to its high medicinal benefits, it is the most essential vegetable crop. The findings of this study indicated that the germination percentage of the bitter melon variety i.e. Bitter gourd-1 (BG-1) was highly affected by the application of different concentrations of plant hormone. Such an effect was even prominent in comparison without the application of plant hormones. The seed germination was significantly highest (96.4 %) @ NAA 0.9 (900 mg/1000 ml). The germination time (days) was significantly lower 5.10 days @ NAA 0.3 (300 mg/1000 ml) and consistently increased at higher concentration of PGR (7.46 days at NAA 0.6 (600 mg/1000 ml) and 8.53 days at 1.5 (1500 mg/1000 ml), respectively. The germination index was 1.91 recorded higher at the control treatment. The results further indicated that the germination index of bitter gourd increased as the concentration of PGR increased. Overall, these findings indicated that the impact of PGR on the germination index was obvious, and the index enhanced as PGR concentration increased. The seedling vigour index was significantly maximum 1835 recorded at NAA 0.3 (300 mg/1000 ml) and followed by NAA 1.5 (1500 mg/1000 ml) with 1292, respectively. The results further showed that the seedling vigour index of bitter gourd decreased between 709 and 1024 at the control and distilled water treatments. We concluded that seed priming is a tool for sustainable agriculture.